Analisis Analisis Kesulitan Belajar Bahasa Arab Pada Maharah Kalam Siswa Kelas V di Madrasah Ibtidaiyah Al-Ihsan Pontianak Tahun Pelajaran 2021/2022 - Melania Khoiriyah; Moh Yusuf Hidayat; Rahnang Rahnang (Armala, 2022)
Abstract : The problem this research is the low ability to speak Arabic students. The purpose of this research are: 1) to identify the process of learning Arabic in speaking skills students of class V; 2) to describe the difficulties of students in learning Arabic in speaking skills class V; 3) to find out the teacher's efforts in dealing with the difficulties of learning Arabic in the speaking skills of class V. This research uses qualitative descriptive research methods with the type of field research. The data sources of this study are class V students and teachers of Arabic subjects. Data collection techniques in this research is observation, interviews and documentation. The results of this research are: 1) the process of learning Arabic in the preliminary activities, the core and closing activities of the teacher have carried out learning activities ideally based on the theory of learning activities; 2) the difficulties experienced by students in terms of linguistics, namely; difficulty distinguishing the sounds of letters whose pronunciation is almost the same as ع، غ، خ، ج، ش، ث، ص،ض; stammering pronunciation of the vocabulary contained in the letters ع،ح،خ،ز; difficulties in the meaning of a word or sentence, understanding the formation of a word. Nonlinguistic aspects; different levels of intellectual abilities of students exist, the student's learning motivation is moderate, lack of self-confidence, low high interest in learning, the student environment is passively speaking Arabic; lack of support from the family, lack of strong encouragement in learning Arabic. Keywords: Difficulty Learning Arabic, Speaking Skills in Arabic